A global survey of bacterial type III secretion systems and their effectors. (10th May 2017) - Hu, Yueming; Huang, He; Cheng, Xi; Shu, Xingsheng; White, Aaron P.; Stavrinides, John; Köster, Wolfgang; Zhu, Guoqiang; Zhao, Zhendong; Wang, Yejun
Summary: The type III secretion system (T3SS) is an important genetic determinant that mediates interactions between Gram‐negative bacteria and their eukaryotic hosts. Our understanding of the T3SS continues to expand, yet the availability of new bacterial genomes prompts questions about its diversity, distribution and evolution. Through a comprehensive survey of ∼20 000 bacterial genomes, we identified 174 non‐redundant T3SSs from 109 genera and 5 phyla. Many of the bacteria are environmental strains that have not been reported to interact with eukaryotic hosts, while several species groups carry multiple T3SSs. Four ultra‐conserved Microsynteny Blocks (MSBs) were defined within the T3SSs, facilitating comprehensive clustering of the T3SSs into 13 major categories, and establishing the largest diversity of T3SSs to date. We subsequently extended our search to identify type III effectors, resulting in 8740 candidate effectors. Lastly, an analysis of the key transcriptional regulators and circuits for the T3SS families revealed that low‐level T3SS regulators were more conserved than higher‐level regulators. This comprehensive analysis of the T3SSs and their protein effectors provides new insight into the diversity of systems used to facilitate host‐bacterial interactions.